Institutional arrangements for the effective development of southern Africa's water resources - Thamae, Lenka (International Food Policy Research Institute, 1997)
Lack of water resources is beginning to limit socioeconomic development i n most parts of the world, and Southern Africa is no exception. If the region's current annual population growth rate of close to 3 percent continues, it has been estimated that most of the countries in Southern Africa will suffer from water shortages by the year 2020 (IUCN, SADC-ELMS, and SARDC 1994). This region faces the added complication that most of its important rivers, lakes, and aquifers are shared by two or more countries. Therefore, dealing with the reality of scarce water will require replacing the current utilitarian, project-based approach to development and management of water resources with a holistic and integrated approach, taking into account future and regional needs as well as current national requirements.